The Impact of Leisure Sports Recreation Resource Value on Recreation Intention of Recreationists - Ang Li; Yubao Xi; Yankai Huang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In pursuit of enhancing the satisfaction assessment of urban greenway visitors in City A and fostering their inclination to revisit the greenway, this research endeavours to examine the influence of the value of leisure sports recreation resources on the recreational intentions of participants. The assessment of recreational satisfaction is proposed to encompass four fundamental factors: namely, greenway recreational facilities, greenway landscape environment, greenway management, and greenway accessibility. The author employs the greenway within City A as a case study to investigate the correlation between greenway recreational satisfaction and the inclination to revisit. Through thorough investigation and analysis, it is observed that a significant proportion of recreational users are local residents residing in proximity to the greenway. Their primary aim is to engage in leisure and fitness activities within a favourable environment, demonstrating a strong willingness to revisit. Consequently, data from 316 respondents were collected, utilizing both qualitative and quantitative research methodologies. The SPSS statistical software was employed for reliability testing and regression analysis purposes. According to the regression analysis conducted using SPSS, it was found that greenway recreational amenities, the quality of the green landscape environment, and the effectiveness of greenway management practices exert positive and statistically significant effects on the inclination to revisit. Conversely, the accessibility of greenway management displayed a negative and statistically insignificant impact on recreational willingness to return. With the exception of one factor, all satisfaction indicators exhibit a noteworthy positive influence on the inclination to revisit, with landscape environment satisfaction emerging as the primary influential factor, followed by the greenway management factor and accessibility factor, both exerting comparatively lesser impact than recreational facilities. Hence, in light of the research outcomes, addressing the issue of greenway management accessibility is deemed crucial, given its demonstrated negative and inconsequential impact on recreational engagement willingness. It is imperative to channel efforts towards enhancing accessibility to ensure a more favourable visitor experience and elevate the probability of their return.